Antigen-Pulsed CpG-ODN-Activated Dendritic Cells Induce Host-Protective Immune Response by Regulating the T Regulatory Cell Functioning in Leishmania donovani-Infected Mice: Critical Role of CXCL10 - Majumder, Saikat; Bhattacharjee, Amrita; Paul Chowdhury, Bidisha; Bhattacharyya Majumdar, Suchandra; Majumdar, Subrata (Frontiers in Immunology, 2014)
Visceral leishmaniasis (VL), caused by Leishmania donovani, is a systemic infection of reticulo-endothelial system. There is currently no protective vaccine against VL and chemotherapy is increasingly limited due to appearance of drug resistance to first line drugs such as antimonials and amphotericin B. In the present study, by using a murine model of leishmaniasis we evaluated the function played by soluble leishmanial antigen (SLA)-pulsed CpG-ODN-stimulated dendritic cells (SLA–CpG–DCs) in restricting the intracellular parasitic growth. We establish that a single dose of SLA–CpG–DC vaccination is sufficient in rendering complete protection against L. donovani infection. In probing the possible mechanism, we observe that SLA–CpG–DCs vaccination results in the significant decrease in Foxp3+GITR+CTLA4+CD4+CD25+ regulatory T cells (Treg) cell population in Leishmania-infected mice. Vaccination with these antigen-stimulated dendritic cells results in the decrease in the secretion of TGF-β by these Treg cells by possible regulation of the SMAD signaling. Moreover, we demonstrate that a CXC chemokine, IFN-γ-inducible protein 10 (IP-10; CXCL10), has a direct role in the regulation of CD4+CD25+ Treg cells in SLA–CpG–DC-vaccinated parasitized mice as Treg cells isolated from IP-10-depleted vaccinated mice showed significantly increased TGF-β production and suppressive activity.